Low Expression of FAM96B is Associated with Poor Prognosis in Hepatocellular Carcinoma - Tang, Yuqun; Tang, Liangke; Du, Haijian; Wu, Chaosheng; Wang, Zhuangxiong; Luo, Guanshui; He, Ke (Turkish Journal of Gastroenterology, 2024)
Background/Aims: Recently, studies on FAM96B functions mainly focused on its role in maintaining the normal physiological function of cells. However, the clinical implications of FAM96B in hepatocellular carcinoma (HCC) are still unclear. Materials and Methods: FAM96B mRNA expression was detected in human HCC tissues and the matched nontumorous tis sues by quantitative real-time reverse transcription (qRT-PCR) and then validated in The Cancer Genome Atlas (TCGA) data base. Immunohistochemistry assay (IHC) was performed on all 137 cases of HCC samples to examine the protein level of FAM96B. Subsequently, the associations between FAM96B expression and clinicopathological parameters and prognosis were further analyzed. Results: The mRNA level of FAM96B was found to be significantly lower in HCC tissues compared to non-tumorous tissues, as observed in both the local hospital and TCGA datab ase.I mmuno histo chemi stry assay analysis revealed a decrease in FAM96B expression in 78 out of 137 cases, which was significantly associated with larger tumor size, higher Barcelona clinic liver cancer or Child stage, and early distant metastasis. Patients with low FAM96B levels tended to have an unfavorable disease-free and overall survival. Moreover, FAM96B was identified as an independent predictor of patient prognosis in both univariate and multivariate survival analyses. Mechanistically, FAM96B was found to inhibit cancer progression by inducing apoptosis in liver cancer cells and inhibiting their growth. Conclusion: Our findings provide the first evidence suggesting the involvement of FAM96B in the progression of HCC. Additionally, FAM96B could potentially serve as a marker for tumor recurrence and prognosis in HCC patients. Cite this article as: Tang Y, Tang L, Du H, et al. Low expression of FAM96B is associated with poor prognosis in hepatocellularcarcinoma. Turk J Gastroenterol. 2025;36(4):255-262.